Unmet Need for Contraception - Mills, Samuel; Bos, Ed; Suzuki, Emi (Washington, DC: World Bank, 2012)
The concept of 'unmet need for contraception', which refers to the proportion of women who do not want to become pregnant but are not using contraception, has been used in the international population field since the 1960s. The concept was developed from the first family planning and fertility surveys conducted in developing countries, which found a disconnect between women's knowledge, attitudes, and practices (KAP) about contraception. Unmet need for contraception is one of several frequently used indicators for monitoring of family planning programs, and was recently added to the millennium development goal of improving maternal health. Some other indicators that are used in combination with unmet need are the contraceptive prevalence rate (CPR), the method mix, sources of contraceptive supplies, and reasons for not using contraception. In this note, authors deal mainly with the unmet need indicator, but believe that other indicators should also be part of monitoring and evaluation of family planning programs to broaden the understanding of the use of family planning in countries.